Training and Development Costs, Staff Costs and Operational Profitability in Nepalese Commercial Banks - Adhikari, Naba Raj (Management Dynamics, 2020)
The main aim of this study was to identify examine the relationship between staff trainings and development costs, total staff costs and the operational profit of Nepalese commercial banks. Six commercial banks has been taken for the study using purposive sampling technique from the total population consisting two government owned banks, two joint venture banks and the rest from private commercial banks. Training and development costs, staff costs and operational profit (before tax) has been defined as the variables of the study. Data have been collected from the annual reports of respective banks covering for the financial year 2016/2017 to 2019/2020. This study found that private commercial banks have focused on training and development to their staff. The staff costs of private banks has been highly explained by training and development costs and it has resulted higher positive impact of staff cost with operational profit.